Teacher training in a contemporary key (Praxis Educativa, 2022)
This paper that I share arises as a result of the doctoral thesis “Teacher training in the face of digital culture. The convenient, the desirable, the possible” (2009-2014). The central thesis that supported it was to connect the voice of experts in the field of Educational Technology and teacher training, in the context of Argentine public educational policies. I write this in complex times; times of pandemic, of anguish, sadness and uncertainties. I took the impulse to share it in the face of this context that has made many changes in our daily lives. In parallel, demands, requirements and needs arose before them. I add a passionate voice to the conversation whose hashtag (#) is teacher training in times of change and uncertainties to make hear a series of conceptual constructions building in practices that allow conversation, dialogue, reflection, rethinking the trade and teacher training in our country in times of digital culture.
Keywords: teacher training; educational technology; digital culture; knowledge; teaching